Dictionary of corruption - Barrington, Robert; David-Barrett, Elizabeth; Dobson Phillips, Rebecca; Garrod, Georgia (Agenda Publishing, 2024)
Written by an expert team, the Dictionary of Corruption is a comprehensive resource for students, academics, practitioners and professionals. It establishes a common interpretation of the language and terminology in the field of corruption and anti-corruption studies. From bribery to Watergate, amakudari to zero tolerance and from anti-corruption agencies to whistleblowing, the Dictionary provides explanations of over 300 key terms, events and case studies
Title from publisher's bibliographic system (viewed on 19 Dec 2024)
Keywords: Corruption / Dictionaries